(Un)Tangled: Exploring the Asymmetric Coevolution of New Venture Capital Firms' Reputation and Status. (September 2015) - Pollock, Timothy G.; Lee, Peggy M.; Jin, Kyuho; Lashley, Kisha
We explore the relationship between status and reputation, examining how its dynamics change over time as these two intangible assets coevolve and how reputation and status are influenced by participation in highly visible events. Using a sample of more than 400 newly founded venture capital (VC) firms, we find that reputation and status positively influence each other but that reputation has a greater effect on status, particularly when firms are older. We also find that the effect of past status on current status weakens as VC firms age, but the relationship between past and current reputation remains consistent with age. Furthermore, our findings show that participating in big hits—blockbuster initial public offerings—has a positive relationship with status when firms are young and a positive relationship with reputation when firms are older, and it helps low-status and low-reputation firms more than it helps high-status and high-reputation firms. This study helps differentiate status and reputation, shows how they coevolve, and provides insight into how new firms build these important intangible assets.